2021
DOI: 10.1016/j.ejogrb.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the COVID-19 outbreak on European trainees in obstetrics and gynaecology: A survey of the impact on training and trainee

Abstract: The purpose of this study is to evaluate how the obstetrics and gynaecology residency program and trainees have been affected by the Corona Virus pandemic in Europe. Study Design: This study is a cross-sectional explorative survey using an online questionnaire. The questionnaire comprised of 40 questions that were subdivided into 4 subjects; workload, specialist training aspects in obstetrics and gynaecology, health and safety of the trainee and women's health and maternal health issues. Inclusion criteria co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
(20 reference statements)
6
16
2
Order By: Relevance
“…Recent studies from disciplines like surgery and radiology have revealed a substantial influence on residents' training workflow during the outbreak. 4 Therefore, this study was planned to assess the outcome of COVID pandemic on the training curriculum of residents posted in Obstetrics and Gynecology (OBG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from disciplines like surgery and radiology have revealed a substantial influence on residents' training workflow during the outbreak. 4 Therefore, this study was planned to assess the outcome of COVID pandemic on the training curriculum of residents posted in Obstetrics and Gynecology (OBG).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from disciplines like surgery and radiology have revealed a substantial influence on residents' training workflow during the outbreak. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The implemented changes in working routines resulted also in negative effects on the employees’ working conditions, which could explain the adverse effects on health described by others [7] , [11] , [12] , [13] , [14] , [15] . Important factors from the qualitative analyses, which could help to understand these negative effects, were worry about being infected and uncertainty whether the implemented changes were sufficient to protect the employees and women from getting COVID-19, as well as shortfalls in the physical care environment, staff shortages, challenges in communicating the rapid changes in work routines, lack of recovery due to extra shifts, and a fear of making mistakes when being transferred to another department.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is limited knowledge about how the COVID-19 pandemic has affected the working conditions for HCWs working in hospital-based maternity and neonatal health care [7] , [11] . Since the beginning of the pandemic, a few cross-sectional studies have been performed, consistently reporting both affected work routines and increased levels of stress and worry among HCWs working in hospital-based maternity and neonatal health care [7] , [11] , [12] , [13] , [14] , [15] . However, these studies do not provide in-depth discussion regarding plausible mechanisms, nor do they give suggestions regarding preventive measures that could reduce the negative effect of the pandemic on HCWs’ working conditions and health [7] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Much of this was significantly curtailed during this period [47]. Reports that are related to this from a number of specialties, including obstetrics and gynecology, urology, ophthalmology, pediatrics, gastroenterology, dermatology, cardiology, dentistry, radiology, anesthetics, emergency medicine, etc., have been documented [48][49][50][51] from nearly all populated continents of the world (Figure 5D). Surgical residents have also been severely impacted by the cancellation of non-essential procedures during this period [52].…”
Section: How Covid-19 Impacted Medical and Nursing Training (Topic 5)mentioning
confidence: 97%